Estetika Sakral dalam Tari Bedhaya Ketawang sebagai Media Relasi Manusia dan Dunia Spiritual - Ratnayu, Adela Sukma; Trisakti, Trisakti (Jurnal Cerano Seni : Pengkajian dan Penciptaan Seni Pertunjukan, 2026)
This study aims to analyze the sacred aesthetics of the Bedhaya Ketawang Dance as a medium for connecting humans and the spiritual world in Javanese culture. The study used a Systematic Literature Review (SLR) method with a qualitative descriptive approach. Data were obtained from books, journals, and previous research related to Nusantara aesthetics, Javanese spirituality, and traditional ritual dance. The results show that the sacred aesthetics of the Bedhaya Ketawang Dance are reflected through gentle, slow, and harmonious dance movements and performance symbols that contain spiritual values. The dancer's body functions as both an artistic and symbolic medium, presenting the human relationship with the transcendental world. Performance elements such as floor patterns, the number of dancers, costumes, and gamelan accompaniment shape the aesthetic and spiritual experience in Javanese culture. Thus, the Bedhaya Ketawang Dance is not only an artistic performance but also a representation of human harmony with the spiritual world. Keywords: sacred aesthetics, Bedhaya Ketawang, Javanese spirituality, dance